A Comparative Evaluation of Indonesia and China's Flood Risk Assessment and Disaster Risk Reduction Planning - Arno A. Kuntoro; Reini D. Wirahadikusumah; Patria Kusumaningrum; Ahmad Nur Wahid; Iqbal F. Herlambang; Xu Lilai; Krishna S. Pribadi; Eliza R. Puri; Rusmawan Suwarman; Aden Firdaus; Roi Milyardi; Kevin Immanuel (Salehan Institute of Higher Education, 2026)
Floods are the most frequent disasters caused by combinations of natural and anthropogenic factors. Given the increasing intensity and frequency of floods, especially in Asian mega-urban regions, effective Disaster Risk Reduction (DRR) strategies are critical. This study presents a comparative evaluation of the national flood risk assessment methods in Indonesia and China, followed by a flood risk map analysis calculated using the Chinese and Indonesian standards for flood risk assessment, specifically for a case study in Bandung City, Indonesia. We found that the Chinese standard method produces a broader spatial identification of high flood risk areas, influenced by rainfall intensity and topography, which better represents pluvial flood risks. Meanwhile, the Indonesian method produces localized high flood risk near rivers, which better represents fluvial flood risks. In the case study of Bandung City, the occurrence of pluvial floods was more dominant than fluvial floods. Therefore, the spatial accuracy of the Chinese method was slightly higher than the Indonesian method. The study emphasizes the importance of a national flood assessment method that balances accuracy, data availability, computational resources, and local/regional characteristics to cope with the increasing risk in urbanized flood-prone areas.